Artificial intelligence and autonomous shipping developing the international legal framework - Soyer, Barış; Tettenborn, Andrew (Hart, 2021)
International regulation of shipping and unmanned vessels / Professors S Baughen and A Tettenborn -- International law of the sea and autonomous cargo 'vessels' / Dr Youri van Logchem -- Autonomous ships and private law issues / Professors Barış Soyer and Andrew M Tettenborn -- Unmanned vessels and international conventions for the carriage of goods by sea / Professor Simon Baughen -- Cyber risks, autonomous operations and risk perceptions : is a new liability paradigm required? / Associate Professor George Leloudas -- Product liability : autonomous ships / Associate Professor Roderick Bagshaw -- Maritime autonomous surface ships : marine insurance response to risks / Peter MacDonald Eggers QC -- The future of autonomous shipping - the regulatory challenge / Professor Barış Soyer
Includes bibliographical references and index
2105
Keywords: Recht; Seeschifffahrt; Künstliche Intelligenz; Autonomes Fahrzeug; Schiff; International Convention for the Prevention of Pollution from Ships / (1973); International Convention for the Safety of Life at Sea / (1974 November 1); Ships / Automation; Marine insurance / Law and legislation; Marine pollution / Law and legislation; Law of the sea; Shipping / Safety regulations; Maritime law; Shipping / Technological innovations